Impact of Treatment Technique on Testicular Dose and Sexual Activity in Rectal Cancer Patients - Tejaswi-Siddappa, Poornachandra; Sunkappa, Shamsundar; Kunigal-Puttaswamy, Jagannath; Katke, Aradhana; Ramanand, Nanda; Boraiah, Thejaswini (Brazilian Journal of Oncology, 2024)
Objective To estimate the incidental radiation dose delivered to the testicles in three-dimensional conformal radiotherapy (3DCRT), intensity-modulated radiotherapy (IMRT), and volumetric-modulated arc therapy (VMAT) in rectal cancer patients and its impact on sexual activity using a quality-of-life questionnaire.Materials and Methods The present study included 40 male patients, aged between 25 and 50 years. with locally-advanced rectal cancer, who would undergo neoadjuvant radiotherapy at a dose of 45 Gray (Gy) in 25 fractions (fr) in the supine position. Planning was performed for three techniques: 3DCRT, IMRT, and VMAT. The testicular dose, testicular volume, planning target volume (PTV), the distance of the tumor from the anal verge, and tumor thickness and length in each plan were recorded. A quality-of-life questionnaire pertaining only to sexual activity by the European Organization for Research and Treatment of Cancer–Quality of Life in Colorectal (EORTC QLQ-CR29) and the Functional Assessment of Cancer Therapy–Colorectal (FACT-C) were used to assess the posttreatment effect on sexual life.Results The mean values for tumor length, thickness, and PTV were of 8.9 cm, 1.77 cm and 1,352 cm3 respectively. The mean dose to the right and left testicles (in centigray, cGy) were as follows: 3DCRT – 336.23 and 206.65; IMRT – 165.15 and 140.25; and VMAT – 209.2 and 229.2 respectively. A significant correlation was observed involving the PTV and testicular volume and the incidental testicular dose received. The questionnaire-based analysis of sexual activity included 31 patients who were alive, of whom 27 had resumed their normal sexual life 3 months after the treatment without difficulty (score 4).Conclusion The IMRT showed a significant reduction in the testicular dose when compared to 3DCRT and VMAT. The PTV and testicular volume presented a statistically significant impact on the testicular dose, and the main reason for abstinence was nervousness about disease recurrence.
Keywords: quality of life; toxicity; testis; rectal Neoplasms; radiotherapy; conformal